Fatty acids, food groups and semen variables in men referring to an Italian Fertility Clinic: Cross‐sectional analysis of a prospective cohort study. (8th January 2020) - Ricci, Elena; Noli, Stefania; Ferrari, Stefania; La Vecchia, Irene; Castiglioni, Marta; Cipriani, Sonia; Somigliana, Edgardo; Parazzini, Fabio; Agostoni, Carlo
Abstract: Diet has been suggested as a factor affecting sperm quality, both in healthy and infertile men. To study whether specific food groups and fatty acids (FA) intake were associated with sperm parameters of men from couples referring to an Italian Fertility Clinic, we conducted a cross‐sectional analysis. A semen sample was collected and analysed before proceeding with assisted reproduction. To evaluate food groups and fatty acids intake, we used a questionnaire of food frequency. We calculated odds ratios (OR) and 95% confidence intervals (CI) for abnormal semen parameters. Among 323 men, 19% had semen volume (SV) <1.5 ml, 31% sperm concentration (SC) <15 mil/mL, 33% total sperm count (TSC) <39 mil and 27% sperm progressive motility <32%. Low SC was more frequent in men with higher saturated FA (SFA) and polyunsaturated FA (PUFA) intake. Better SC and TSC were related to higher monounsaturated FA (MUFA)/SFA ratio. Monounsaturated FA and linoleic/linolenic acid ratio were not related to any considered parameters. Low TSC was associated with low vegetable intake. In conclusion, normal sperm parameters were more frequent in men with low intake of SFA and PUFA, and high vegetable intake. Higher MUFA/SFA ratio was associated with better sperm quality parameters.